Acoustophoretic trapping of particles by bubbles in microfluidics - González, Itziar; Candil, Manuel; Luzuriaga, Jon (Frontiers in Physics, 2023)
We present in this paper a simple method to produce strategic acoustic particle capture sites in microfluidic channels in a controlled way. Air bubbles are intermittently injected into a micro-capillary with rectangular cross section during a flow motion of liquid suspensions containing micron-sized particles or particles to create bubble-defined ‘micro-gaps’ with size close to 200 µm and spheroidal geometry. The establishment of a 3D standing acoustic wave inside the capillary at a frequency close to 1 MHz produces different radiation forces on solid particles and bubbles, and acoustic streaming around the bubble. While the sample flows, part of the particles collect along the acoustic pressure node established near the central axis and continue circulating aligned through the capillary until reaching the end, where are released enriched. Meanwhile, the bubble travels very fast toward positions of maximum pressure amplitude beside the channel wall, driven by Bjerkness forces, and attach to it, remaining immovable during the acoustic actuation. Some particles adhere to its membrane trapped by the acoustic streaming generated around the oscillating bubble. Changes of frequency were applied to analyze the influence of this parameter on the bubble dynamics, which shows a complete stability once attached to the channel wall. Only increasing the flow motion induces the bubble displacements. Once reached the open air at the end of the capillary, the bubble disappears releasing the trapped particles separated from their initial host suspension with a purity degree. The device presents a very simple geometry and a low-cost fabrication.